Soft X-ETFE insulating material with low fluorine overflow and preparation method thereof

By introducing dynamic crosslinking agents, functionalized nanoparticles, fluorine capture agents and flexible monomers into the ETFE insulating material, a dynamic reversible crosslinking network and labyrinth effect is solved, and the fluoride migration and flexibility of ETFE insulating material is achieved under high flexibility, high temperature and dynamic operating conditions is achieved, and the high flexibility and long-term stability of the material is achieved.

CN119842143AInactive Publication Date: 2025-04-18HANGZHOU YITIAN TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510315821.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The application of existing ETFE insulating materials under high flexibility, high temperature and dynamic operating conditions is limited, especially fluoride migration problems and balance of flexibility and mechanical properties.

Method used

By introducing dynamic crosslinking agents, functionalized nanoparticles, fluorine capture agents and flexible monomers, a dynamic reversible three-dimensional crosslinking network and maze effect are constructed, and combined with chemical fixation mechanisms, the flexibility of the material and the suppression ability of fluoride migration are improved.

Benefits of technology

It realizes that the material maintains flexibility and flexibility at high temperatures, significantly reduces fluoride migration and release, and improves the long-term high-temperature use stability and mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842143A_ABST
    Figure CN119842143A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials and electrical insulation, and discloses a soft low-fluorine-overflow X-ETFE insulating material which comprises the following components in percentage by mass: 75-85% of X-ETFE resin, 5-8% of a dynamic cross-linking agent, 3-6% of functionalized nanoparticles, 1-3% of a fluorine capturing agent and 5-8% of a flexible monomer. The invention also discloses a preparation method of the soft and low-fluorine-overflow X-ETFE insulating material, and the preparation method comprises the following steps: S1, functionalized nano particle treatment: carrying out surface functionalization treatment on nano particles to enhance the compatibility of the nano particles and X-ETFE resin. Through the synergistic effect of the dynamic cross-linking agent, the functionalized nanoparticles, the fluorine capturing agent and the flexible monomer, high flexibility, low fluoride migration and high-temperature stability of the X-ETFE insulating material are achieved, the technical problem that flexibility and high-temperature resistance are difficult to balance is solved, and the high-performance requirement in an extreme environment is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials and electrical insulation, in particular to a soft, low-fluorine overflow X-ETFE insulating material and a preparation method thereof. Background Art

[0002] Ethylene-tetrafluoroethylene copolymer (ETFE) is a high-performance engineering material. It is widely used in aerospace, high-performance cables and special industrial fields due to its excellent high temperature resistance, chemical corrosion resistance and excellent electrical insulation performance. However, with the continuous improvement of application requirements, especially in complex environments, the existing ETFE insulation materials have exposed obvious deficiencies in some core technical performances. These deficiencies limit its application under high flexibility, high temperature and dynamic conditions.

[0003] The fluoride migration problem is a key defect of existing ETFE insulating materials. Under high temperature conditions, small fluoride molecules inside the ETFE material tend to migrate outward to the surface of the material. This phenomenon is particularly prominent in long-term use. The release of fluoride may directly destroy the electrical insulation properties of the material, and may also cause corrosion and pollution to surrounding equipment and the environment. This migration problem is more serious in high electric field environments, affecting the long-term reliability of the equipment. In current technology, attempts to inhibit fluoride migration are often made by increasing the cross-linking density to constrain the movement of molecular chains. However, this method is not flawless. The increase in cross-linking structure is often accompanied by an increase in the rigidity of the material. As a result, the softness and dynamic properties of the material are significantly reduced, especially in bending or complex stress environments, showing poor adaptability. In addition, under high temperature conditions, the cross-linking network itself may gradually age or break, which causes the inhibition effect of fluoride to decrease significantly over time, and cannot truly meet the long-term needs of demanding application scenarios.

[0004] On the other hand, the balance between softness and mechanical toughness is also an important problem faced by existing ETFE insulating materials. This problem is particularly prominent in extreme temperature environments. In order to improve the high-temperature stability of the material, the existing technology usually enhances the structural strength of the material by adding high-rigidity components or increasing the cross-linking density. However, this method has an obvious cost-the flexibility of the material decreases and the rigidity increases significantly. In low-temperature environments, this rigidity feature is more obvious, which is manifested as the material is easily brittle, loses dynamic adaptability, and even breaks under mechanical stress. This brittle feature greatly limits its application in fields with dynamic bending or high flexibility requirements, such as flexible cables or dynamic sealing components. Some studies have attempted to optimize material properties by introducing flexible monomers or elastomer components, which has indeed improved softness to a certain extent, but this modification method usually sacrifices high temperature resistance and may aggravate the problem of fluoride migration. Therefore, the existing technology has always been unable to achieve a balance between high temperature performance and flexibility performance at the balance point between softness and mechanical properties. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a soft, low-fluorine overflow X-ETFE insulating material and a preparation method thereof, which solves the technical problems of the existing ethylene-tetrafluoroethylene copolymer (ETFE) insulating material in terms of softness, high-temperature stability and fluoride migration control.

[0006] To achieve the above purpose, the present invention is implemented through the following technical scheme: a soft, low-fluorine overflow X-ETFE insulating material, comprising the following components, in terms of mass percentage: X-ETFE resin 75-85%, dynamic cross-linking agent 5-8%, functionalized nanoparticles 3-6%, fluorine capture agent 1-3%, flexible monomer 5-8% and flame retardant 1-2%.

[0007] Preferably, the dynamic cross-linking agent is a compound containing an imine group or a disulfide bond.

[0008] Preferably, the functionalized nanoparticles are boron nitride, graphene oxide or silicon dioxide, and have a particle size of 20-50 nm.

[0009] Preferably, the flexible monomer is polydimethylsiloxane.

[0010] Preferably, the fluorine scavenger is an amino compound or a zinc complex.

[0011] Specifically, X-ETFE resin, as a matrix material, provides excellent high temperature resistance, chemical corrosion resistance and good electrical insulation properties. As the main component, its polymer structure ensures the mechanical stability and electrical insulation properties of the material in harsh environments, providing a stable matrix support for the functions of other components.

[0012] The dynamic crosslinker is one of the core modified components of the present invention, which constructs a dynamic three-dimensional crosslinked network through reversible imine bonds or disulfide bonds. Under high temperature or external force, these reversible bonds can break to release stress, and then recombine after the environment is restored, giving the material excellent flexibility and deformation recovery ability. Compared with traditional chemical crosslinkers, its dynamic characteristics avoid the rigidity and embrittlement problems caused by high crosslinking density, allowing the material to maintain flexibility in high temperature environments and adapt to complex stress conditions.

[0013] The introduction of functionalized nanoparticles significantly improves the material's barrier capacity to small molecular fluorides through the maze effect. Boron nitride, graphene oxide or silicon dioxide are selected as nanoparticles. These materials have high specific surface area and excellent thermal stability. After functionalization, the surface polar groups form a good interface with the matrix material, enhancing dispersibility and compatibility. The particle size is controlled at 20-50nm, which not only avoids agglomeration, but also ensures the formation of a uniform reinforcement structure in the matrix, thereby effectively extending the migration path of fluorides, reducing the diffusion rate, and improving mechanical properties.

[0014] Fluorine scavengers fix fluoride through chemical reactions, and their core function is to inhibit fluoride migration from a chemical level. Amino compounds or zinc complexes are preferred, as they can form stable complexes with free fluoride, completely solving the shortcomings of relying solely on physical barrier methods. Fluorine scavengers can still maintain chemical stability in high-temperature environments, further enhancing the insulation properties of the material, and are particularly suitable for long-term high-temperature use scenarios.

[0015] The introduction of flexible monomers significantly reduces the glass transition temperature of the material by introducing flexible segments (such as polydimethylsiloxane) into the molecular chain, and improves the activity of the molecular chain in low temperature environments, thereby giving the material better flexibility and low-temperature deformation ability. In addition, as a buffer unit in the dynamic cross-linked network, the flexible monomer can disperse the damage to the cross-linked network caused by external forces, further improving the comprehensive mechanical properties of the material. Its role makes the material have excellent softness under both high and low temperature conditions.

[0016] The addition of flame retardants improves the safety performance of the material and ensures that the material has good flame retardant effect in high temperature or fire environment. Due to the small amount used and stable properties, the introduction of flame retardants will not significantly affect the flexibility or other properties of the material, while meeting the needs of high insulation safety application scenarios. A method for preparing a soft, low-fluorine overflow X-ETFE insulating material comprises the following steps: S1. Functionalized nanoparticle treatment: surface functionalization of the nanoparticles to enhance their compatibility with the X-ETFE resin; S2, raw material mixing: X-ETFE resin, dynamic cross-linking agent, flexible monomer, functionalized nanoparticles and fluorine capture agent are uniformly mixed according to the mass percentage ratio; S3, melt blending: melt blending the mixture in a twin-screw extruder at an extrusion temperature of 200-260° C. and a screw speed of 50-150 rpm; S4, dynamic crosslinking reaction: subjecting the melt blended materials to dynamic crosslinking reaction at 260-300°C for 10-15 minutes; S5, molding and cooling: the material is quickly cooled after molding, and the cooling medium temperature is -10℃ to 0℃ Preferably, the functionalized nanoparticle treatment in step S1 includes the following process: S1.1, adding nanoparticles into deionized water and stirring to form a suspension; S1.2, adding silane coupling agent for surface modification, the reaction temperature is 50-60℃, the pH value is 4-6, and the time is 6-8h; S1.3, washing and vacuum drying to obtain functionalized nanoparticles.

[0017] Preferably, the raw material mixing in step S2 is carried out in a high-speed mixer with a rotation speed of 1000-2000 rpm and a mixing temperature of room temperature to 60°C.

[0018] Preferably, the temperature of the twin-screw extruder for melt blending in step S3 is distributed along the axial direction as follows: 200-220° C. in the feeding zone, 220-240° C. in the mixing zone, and 240-260° C. in the discharge zone.

[0019] Preferably, the cooling medium in step S5 is coolant or air, and the cooling time is 10-20 minutes.

[0020] The present invention provides a soft, low-fluorine overflow X-ETFE insulating material and a preparation method thereof, which has the following beneficial effects: 1. By introducing a dynamic cross-linking agent, a dynamic reversible three-dimensional cross-linked network structure is constructed inside the material. The dynamic cross-linking agent enables the material to achieve local breakage and reorganization under high temperature and external force through the reversible reaction of imine bonds or disulfide bonds. This mechanism allows the molecular chain segments to release tension under stress and re-form a stable cross-linked network after the environment is restored, thereby significantly improving the flexibility and deformation recovery ability of the material. Compared with the X-ETFE insulating material using the traditional chemical cross-linking method in the prior art, the present invention effectively avoids the problem of excessive rigidity of the cross-linked network, solves the problem of embrittlement and breakage of the material caused by high cross-linking density, and enables the insulating material to maintain flexibility at high temperatures and withstand repeated deformation.

[0021] 2. The present invention introduces functionalized nanoparticles, which form a tight bond with the matrix material through the physical enhancement effect at the nanoscale. The functionalization treatment generates polar groups on the surface of the nanoparticles, thereby forming a good interface bond with the X-ETFE resin. After these nanoparticles are evenly distributed in the matrix, the migration path of small molecular fluorides is extended through the maze effect, which significantly reduces the diffusion rate of fluorides. At the same time, its high specific surface area significantly increases the barrier capacity to fluorides. Unlike the direct addition of unmodified micron-sized fillers in the prior art, the present invention not only solves the problems of poor filler dispersibility and low compatibility with the matrix, but also achieves a higher fluoride migration inhibition effect while maintaining the flexibility of the material, which is particularly suitable for application scenarios with high temperature and high insulation requirements.

[0022] 3. The present invention innovatively achieves chemical fixation of fluoride by introducing a fluorine scavenger. The scavenger can complex with free fluoride inside the matrix to generate a stable chemical complex, thereby solving the problem of fluoride migration from a chemical level. Compared with the prior art solutions that simply rely on physical barriers or filler additions to limit fluoride migration, the present invention significantly improves the efficiency of fluoride capture and remains stable under high temperature conditions. The chemical complexation not only solves the technical difficulty of the inability to effectively control fluoride migration under high temperature environments, but also avoids the problem of reduced insulation performance caused by long-term migration of fluoride, thereby ensuring the chemical stability of the material during long-term use.

[0023] 4. The present invention uses the synergistic effect of flexible monomers and dynamic cross-linking agents to make the material have both high flexibility and dynamic stability in structure. The flexible monomer reduces the glass transition temperature of the material by introducing flexible segments into the molecular chain, so that the molecular chain segments still maintain sufficient activity at low temperatures, thereby improving the low-temperature flexibility of the material. At the same time, the flexible monomer plays the role of a buffer unit in the dynamic cross-linking network, effectively reducing the damage of the cross-linking network by external forces. Compared with the high cross-linking density materials with greater rigidity in the prior art, the soft X-ETFE insulating material of the present invention still has excellent softness under low temperature and complex deformation conditions, solving the technical bottleneck of traditional insulating materials being easy to crack and limited in deformation under low temperature environments, and can meet the actual needs of extreme environments such as aerospace and high-flexible cables. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the method flow of the present invention. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Please see attached Figure 1 The embodiment of the present invention provides a soft, low-fluorine overflow X-ETFE insulating material, comprising the following components, by mass percentage: 75-85% X-ETFE resin, 5-8% dynamic cross-linking agent, 3-6% functionalized nanoparticles, 1-3% fluorine capture agent, 5-8% flexible monomer and 1-2% flame retardant.

[0027] Dynamic cross-linking agents are compounds containing imine groups or disulfide bonds.

[0028] The functionalized nanoparticles are boron nitride, graphene oxide or silicon dioxide, and the particle size thereof is 20-50 nm.

[0029] The flexible monomer is polydimethylsiloxane.

[0030] The fluorine scavenger is an amino compound or a zinc complex.

[0031] A method for preparing a soft, low-fluorine overflow X-ETFE insulating material comprises the following steps: S1. Functionalized nanoparticle treatment: surface functionalization of the nanoparticles to enhance their compatibility with the X-ETFE resin; S2, raw material mixing: X-ETFE resin, dynamic cross-linking agent, flexible monomer, functionalized nanoparticles and fluorine capture agent are uniformly mixed according to the mass percentage ratio; S3, melt blending: melt blending the mixture in a twin-screw extruder at an extrusion temperature of 200-260° C. and a screw speed of 50-150 rpm; S4, dynamic crosslinking reaction: subjecting the melt blended materials to dynamic crosslinking reaction at 260-300°C for 10-15 minutes; S5. Molding and cooling: After molding, the material is quickly cooled, and the temperature of the cooling medium is -10℃ to 0℃.

[0032] The functionalized nanoparticles treatment in step S1 includes the following processes: S1.1, adding nanoparticles into deionized water and stirring to form a suspension; S1.2, adding silane coupling agent for surface modification, the reaction temperature is 50-60℃, the pH value is 4-6, and the time is 6-8h; S1.3, washing and vacuum drying to obtain functionalized nanoparticles.

[0033] In step S2, the raw materials are mixed in a high-speed mixer at a rotation speed of 1000-2000 rpm and a mixing temperature of room temperature to 60°C.

[0034] The temperature of the twin-screw extruder for melt blending in step S3 is distributed along the axial direction as follows: 200-220° C. in the feeding zone, 220-240° C. in the mixing zone, and 240-260° C. in the discharge zone.

[0035] The cooling medium in step S5 is coolant or air, and the cooling time is 10-20 minutes.

[0036] Example 1: Preparation of soft, low-fluorine overflow X-ETFE insulation material Material formula: This embodiment is prepared according to the following ratio: X-ETFE resin 80%; dynamic cross-linking agent (imine compound) 7%; functionalized nanoparticles (graphene oxide, particle size 30nm) 4%; fluorine scavenger (amino compound) 2%; flexible monomer (polydimethylsiloxane) 6%; flame retardant (antimony trioxide) 1%.

[0037] Preparation steps: S1. Functionalization of nanoparticles: Weigh 10 g of graphene oxide powder, add it to 100 mL of deionized water and stir for 20 min to make a suspension. Add silane coupling agent (KH550) in an amount of 4% of the mass of graphene oxide. Adjust the pH value of the solution to 5 and react in a 50°C water bath for 6 h. After the reaction, wash it with ethanol three times and vacuum dry it to obtain functionalized nanoparticles.

[0038] S2, raw material mixing: Add X-ETFE resin, dynamic crosslinking agent and flexible monomer into a high-speed mixer, stirring temperature is 40°C, speed is 1200rpm, and mixing time is 10min. Then add functionalized nanoparticles, fluorine scavenger and flame retardant, continue stirring for 5min, and obtain a uniform mixture.

[0039] S3, melt blending: the mixed material is fed into a twin-screw extruder, the feeding zone temperature is 210°C, the mixing zone temperature is 230°C, and the discharge zone temperature is 250°C. The screw speed is set to 80rpm, and the extrusion speed is 5kg / h. After extrusion, a uniformly molten material is obtained.

[0040] S4, dynamic cross-linking reaction: the extruded material is transferred to a heat curing furnace and subjected to a dynamic cross-linking reaction at 280°C for 12 minutes. During the reaction, the dynamic cross-linking agent forms a reversible cross-linking network.

[0041] S5, molding and cooling: The material is processed into sheets by a molding machine, the molding temperature is 260℃, and the pressure is 8MPa. After molding, it is immediately placed in a coolant (temperature -5℃), and the cooling time is 15min to obtain a finished product.

[0042] Example 2: Preparation of soft and highly flexible insulating cable material Material formula: The components and ratios of this embodiment are as follows: X-ETFE resin 75%; dynamic cross-linking agent (containing disulfide bond compound) 6%; functionalized nanoparticles (boron nitride, particle size 25nm) 5%; fluorine scavenger (zinc complex) 3%; flexible monomer (polydimethylsiloxane) 8%; flame retardant (antimony trioxide) 2%.

[0043] Preparation steps: S1. Preparation of functionalized nanoparticles: 10 g of boron nitride powder was added to deionized water and ultrasonically dispersed for 30 min. Silane coupling agent KH560 (3% of the mass of boron nitride) was added and the pH value was adjusted to 4.5. After stirring at 60°C for 7 h, the mixture was centrifuged and dried to obtain functionalized boron nitride.

[0044] S2. Material mixing: Mix X-ETFE resin, dynamic crosslinking agent and flexible monomer in a high-speed mixer at a speed of 1500 rpm for 8 minutes. Then add functionalized boron nitride, fluorine scavenger and flame retardant, and continue mixing for 3 minutes to form a uniform mixture.

[0045] S3. Melt blending: The mixed material is melted and plasticized in a twin-screw extruder, with the feeding zone temperature at 200°C, the mixing zone temperature at 220°C, and the discharge zone temperature at 240°C. The screw speed is 60rpm to ensure uniform dispersion.

[0046] S4. Cross-linking reaction: Heat the material to 290°C in a dynamic cross-linking device and keep it warm for 10 minutes to form a dynamic reversible cross-linking network.

[0047] S5. Molding and cooling: The molten material is extruded into a cable sheath through a die, and is cooled in a 0°C coolant for 10 minutes before being rolled up.

[0048] Example 3: Preparation of low fluorine overflow flexible sheet material Material formula: The component ratios of this embodiment are: X-ETFE resin 85%; dynamic cross-linking agent (imine compound) 5%; functionalized nanoparticles (graphene oxide) 3%; fluorine scavenger (amino compound) 2%; flexible monomer (polydimethylsiloxane) 5%; flame retardant 1%.

[0049] Preparation steps: S1. Functionalization treatment: Add deionized water to graphene oxide, stir to make a suspension, add KH550 (5% of the mass of graphene oxide), stir at 55° C. for 6 h to obtain functionalized graphene oxide.

[0050] S2. Material mixing: premix the X-ETFE resin and the flexible monomer for 10 minutes, then add the functionalized nanoparticles, fluorine capture agent and dynamic crosslinking agent, stir evenly, and the mixing temperature is 50°C.

[0051] S3. Melt blending: In a twin-screw extruder, the material was extruded at a feeding zone temperature of 220° C., a mixing zone temperature of 240° C., a discharge zone temperature of 260° C., and a screw speed of 70 rpm.

[0052] S4, cross-linking reaction: the extruded material is transferred into a heat treatment furnace and reacted at 280°C for 15 minutes to form a dynamic cross-linking network.

[0053] S5. Molding and cooling: The material is molded into a sheet with a thickness of 2 mm, the coolant temperature is -10°C, and the cooling time is 12 minutes.

[0054] Example 4: Preparation of dynamically cross-linked composite materials Material formula: X-ETFE resin 78%; dynamic cross-linking agent (containing imine compounds) 6%; functionalized nanoparticles (boron nitride) 4%; fluorine scavenger (zinc complex) 2%; flexible monomer (polydimethylsiloxane) 8%; flame retardant (antimony trioxide) 2%.

[0055] Preparation steps: S1. Nanoparticle functionalization: Boron nitride powder is treated with KH560 at 60°C, pH 5, and time 8h. After treatment, it is dried for later use.

[0056] S2. Material mixing: In a high-speed mixer, X-ETFE and the flexible monomer are first mixed for 10 minutes, and then functionalized boron nitride, fluorine scavenger and dynamic cross-linking agent are added and mixed evenly.

[0057] S3. Extrusion blending: The temperature range of the twin-screw extruder is 200°C-250°C, and the screw speed is set to 80 rpm.

[0058] S4. Cross-linking treatment: The extruded material is subjected to a cross-linking reaction at 290°C for 12 minutes to form a dynamic reversible network.

[0059] S5, Sheet forming and cooling: The material is formed in the molding machine with a thickness of 1 mm and a coolant temperature of 0°C.

[0060] Comparative Example 1: Preparation process without using a dynamic cross-linking agent process: Formula difference: The dynamic cross-linking agent is omitted, and the rest of the formula is consistent with Example 1: X-ETFE resin 80%; functionalized nanoparticles (graphene oxide) 4%; fluorine scavenger (amino compound) 2%; flexible monomer (polydimethylsiloxane) 6%; flame retardant (antimony trioxide) 1%.

[0061] Steps: Nanoparticle functionalization: Graphene oxide was treated according to the functionalization method of Example 1 to ensure uniform dispersion.

[0062] Material mixing: X-ETFE resin, flexible monomer, functionalized nanoparticles, fluorine scavenger and flame retardant were mixed at a mixer speed of 1200 rpm, a temperature of 40° C., and a time of 10 min.

[0063] Melt blending: twin-screw extruder, feeding zone temperature 210°C, mixing zone temperature 230°C, discharge zone temperature 250°C, screw speed 80 rpm.

[0064] Molding cooling: molding temperature 260℃, pressure 8MPa, coolant temperature -5℃, cooling time 15min.

[0065] Comparative Example 2: Preparation process without using functionalized nanoparticles process: Formula difference: functionalized nanoparticles are omitted, and the rest of the formula is consistent with Example 2: X-ETFE resin 75%; dynamic cross-linking agent (containing disulfide bond compound) 6%; fluorine scavenger (zinc complex) 3%; flexible monomer (polydimethylsiloxane) 8%; flame retardant (antimony trioxide) 2%.

[0066] Steps: Mixing: X-ETFE resin, dynamic cross-linking agent, flexible monomer, fluorine scavenger and flame retardant are directly mixed in a high-speed mixer at a speed of 1500 rpm for 10 minutes.

[0067] Melt blending: the twin-screw extruder had a feeding zone temperature of 200°C, a mixing zone temperature of 220°C, a discharge zone temperature of 240°C, and a screw speed of 60 rpm.

[0068] Cross-linking reaction: dynamic cross-linking temperature 290°C, time 10 min.

[0069] Cooling molding: molding temperature 260℃, coolant temperature 0℃, cooling 10min.

[0070] Comparative Example 3: Preparation process without using fluorine scavenger process: Formula difference: omitting the fluorine scavenger, the rest of the formula is consistent with Example 3: X-ETFE resin 85%; dynamic cross-linking agent (imine compound) 5%; functionalized nanoparticles (graphene oxide) 3%; flexible monomer (polydimethylsiloxane) 5%; flame retardant: 1%.

[0071] Steps: Nanoparticle functionalization: Graphene oxide was treated according to the functionalization method of Example 3.

[0072] Material mixing: X-ETFE resin, dynamic cross-linking agent, flexible monomer, functionalized nanoparticles and flame retardant were mixed in a high-speed mixer at a speed of 1200 rpm, a temperature of 40° C., and a mixing time of 10 min.

[0073] Melt blending: the twin-screw extruder had a feeding zone temperature of 220°C, a mixing zone temperature of 240°C, a discharge zone temperature of 260°C, and a screw speed of 70 rpm.

[0074] Cross-linking reaction: dynamic cross-linking temperature 280°C, time 12 min.

[0075] Molding cooling: molding temperature 260℃, coolant temperature -10℃, cooling for 12 minutes.

[0076] Comparative Example 4: Preparation process with insufficient content of flexible monomer process: Formula difference: the amount of flexible monomer (polydimethylsiloxane) is reduced to 2%, and the rest of the formula is consistent with Example 1: X-ETFE resin 80%; dynamic cross-linking agent (imine compound) 7%; functionalized nanoparticles (graphene oxide) 4%; fluorine scavenger (amino compound) 2%; flame retardant (antimony trioxide) 1%.

[0077] Steps: Nanoparticle functionalization: same as in Example 1.

[0078] Material mixing: X-ETFE resin, dynamic cross-linking agent, functionalized nanoparticles, fluorine scavenger, flexible monomer (low content) and flame retardant were mixed in a high-speed mixer at a mixing temperature of 40°C, a rotation speed of 1200 rpm and a mixing time of 10 min.

[0079] Melt blending: the twin-screw extruder had a feeding zone temperature of 210°C, a mixing zone temperature of 230°C, a discharge zone temperature of 250°C, and a screw speed of 80 rpm.

[0080] Cross-linking reaction: dynamic cross-linking temperature 280°C, time 12 min.

[0081] Molding cooling: molding temperature 260℃, coolant temperature -5℃, cooling time 15min.

[0082] Comparative Example 5: The particle size of functionalized nanoparticles is too large process: Formula difference: the functionalized nanoparticles are changed to boron nitride with a particle size of 100 nm, and the rest of the formula is consistent with Example 2: X-ETFE resin 75%; dynamic cross-linking agent (containing disulfide bond compound) 6%; fluorine scavenger (zinc complex) 3%; flexible monomer (polydimethylsiloxane) 8%; flame retardant (antimony trioxide) 2%.

[0083] Steps: Functionalization treatment: The same as Example 2, but using boron nitride with a particle size of 100 nm.

[0084] Material mixing: high-speed mixer speed 1500rpm, time 8min.

[0085] Melt blending: the twin-screw extruder had a feeding zone temperature of 200°C, a mixing zone temperature of 220°C, a discharge zone temperature of 240°C, and a screw speed of 60 rpm.

[0086] Cross-linking reaction: dynamic cross-linking temperature 290°C, time 10 min.

[0087] Cooling molding: molding temperature 260℃, coolant temperature 0℃, cooling 10min.

[0088] Experiment 1: Fluoride migration test Experimental description: Experimental purpose: To evaluate the difference in fluoride release between the examples and the comparative examples under high temperature conditions, and to verify the inhibitory effect of the dynamic cross-linking agent, functionalized nanoparticles and fluorine capture agent on fluoride migration.

[0089] Experimental samples: Example: Example 1, Example 2, Example 3 Comparative Examples: Comparative Example 1 (without dynamic crosslinking agent), Comparative Example 2 (without functionalized nanoparticles), Comparative Example 3 (without fluorine capture agent) Experimental equipment: gas chromatography-mass spectrometry (GC-MS), high-temperature inert gas sealed chamber (volume 500mL).

[0090] Experimental steps: Sample preparation: According to the preparation methods of the examples and comparative examples, sheet samples with a thickness of 2 mm and a size of 50 mm×50 mm were prepared, and a standard mold was used to ensure the consistency of the sample size.

[0091] All samples were placed in a drying oven and dried at 50°C for 12 h to remove moisture and ensure the reliability of the test data.

[0092] Testing process: Each group of samples is placed individually in a sealed chamber.

[0093] The chamber temperature was set to 300°C and the sample was kept exposed at this temperature for 2 h. High-purity nitrogen was introduced into the chamber to prevent oxidation and ensure the integrity of the volatiles.

[0094] After the exposure, the gas in the cavity was quickly extracted with a sampling needle and injected into the GC-MS for mass detection of fluoride.

[0095] Data recording and repeated experiments: Each sample was tested three times to reduce accidental errors.

[0096] The average value of fluoride release (unit: mg / g) was recorded.

[0097] Experimental data: Table 1: Comparison of fluoride release between examples and comparative examples Sample No. Fluoride release (mg / g) Repeat test 1 Repeat Test 2 Repeat test 3 Example 1 0.0051 0.0048 0.0055 0.0049 Example 2 0.0062 0.0059 0.0067 0.006 Example 3 0.0058 0.0055 0.006 0.0061 Comparative Example 1 0.0214 0.021 0.0221 0.0212 Comparative Example 2 0.0178 0.0172 0.0183 0.018 Comparative Example 3 0.0146 0.0141 0.0151 0.0147 Summary: The data of Example 1 clearly demonstrates the powerful ability of the dynamic cross-linking network in inhibiting the migration of fluoride. In the absence of a dynamic cross-linking agent, the fluoride release in Comparative Example 1 is as high as 0.0214 mg / g, which is more than 4 times that of Example 1. Without the support of the cross-linking network, the molecular chains lose their restraint at high temperatures, the migration path is short, and fluoride can easily penetrate the material. The dynamic cross-linking agent plays a core role in Example 1, stabilizing the molecular chains through the breaking and recombination of the cross-linking points, so that the release of fluoride is effectively limited. It can be said that this network is not only a constraint, but also a molecular-level filtration mechanism.

[0098] The effect of functionalized nanoparticles is in sharp contrast between Example 2 and Comparative Example 2. The fluoride release of Comparative Example 2 is significantly higher than that of Example 2, reaching 0.0178 mg / g. The functionalization of nanoparticles plays a dual role here: on the one hand, the modified nanoparticles can form a strong interface with the matrix, preventing the "leakage" of fluoride through the interface; on the other hand, the labyrinth effect of the nanoparticles prolongs the diffusion path of small molecules, greatly reducing the migration rate of fluoride. In contrast, Comparative Example 2 lacks this enhancement effect, and the barrier performance of the material is obviously affected.

[0099] Example 3 and Comparative Example 3 demonstrate the chemical fixation effect of the fluorine capture agent. In Comparative Example 3, although the functionalized nanoparticles have a physical barrier effect, the fluoride release is still high, reaching 0.0146 mg / g. In Example 3, the fluorine capture agent fixes the free fluoride through complexation, completely solving the migration problem from a chemical level. The combination of chemical capture and physical barrier is particularly well demonstrated in Example 3, and this multiple synergistic effect is exactly what cannot be achieved in the comparative example.

[0100] Experiment 2: Softness Test Experimental description: Experimental purpose: to test the flexibility performance of the examples and comparative examples under low temperature conditions, to evaluate the contribution of the flexible monomer and dynamic cross-linking agent to the flexibility of the materials, and to focus on verifying the adaptability of the materials in low temperature environments.

[0101] Experimental samples: Embodiment: Embodiment 1, Embodiment 2 Comparative Examples: Comparative Example 1 (without dynamic crosslinking agent), Comparative Example 4 (with reduced flexible monomer content) Experimental equipment: dynamic mechanical analyzer (DMA), cryogenic box (liquid nitrogen cooling, temperature control range -80℃ to room temperature).

[0102] Experimental steps: Sample preparation: The samples of the embodiments and comparative examples were processed into strip samples with a size of 80 mm×10 mm×2 mm.

[0103] The samples were dried at 50 °C for 12 h to remove potential humidity effects.

[0104] Test conditions: The sample was installed in the DMA fixture with a clamping length of 60 mm and the loading method was a three-point bending test.

[0105] The initial test temperature was room temperature (25°C), and the temperature was gradually reduced by 10°C each time until -80°C.

[0106] At each temperature point, the storage modulus (G , ) and loss modulus (G ,, ), the frequency is set to 0.1Hz.

[0107] Testing process: Turn on the DMA equipment, cool the sample to the test temperature with liquid nitrogen, and start data acquisition after the temperature stabilizes.

[0108] During the test, the changes in storage modulus and loss modulus of the sample at different temperature points are recorded.

[0109] Each group of samples was tested 3 times and the average value was taken.

[0110] Data processing: Analyze the variation trend of storage modulus of different samples with temperature.

[0111] The storage modulus at -60°C was compared to evaluate the flexibility of the material in low temperature environment.

[0112] Experimental data: Table 2: Comparison of storage modulus (G,) of the embodiment and the comparative example (unit: MPa) Temperature (℃) Example 1 Example 2 Comparative Example 1 Comparative Example 4 25 31.5 33.2 35.1 33.9 15 38.2 40.1 45.7 41.5 5 49.8 50.3 57.9 53.6 -5 60.9 61.8 72.1 68.4 -15 77.6 79.2 95.4 88.1 -25 102.4 104.5 126.3 115.7 -35 140.7 145.1 174.8 156.2 -45 178.3 183.6 220.4 198.7 -60 214.9 221.5 278.2 245.3 Summary: The presence of a dynamic cross-linking agent is crucial to the low-temperature flexibility of the material. The storage modulus of Comparative Example 1 at -60°C is as high as 278.2MPa, far exceeding the 214.9MPa of Example 1. Without a dynamic cross-linking agent, the molecular chains freeze at low temperatures, becoming rigid and brittle. However, Example 1 uses the breaking and slipping mechanism of dynamic bonds to enable the molecular chains to adapt to external bending stresses at low temperatures. This dynamic network not only improves flexibility, but also delays the complete freezing of the chain segments, significantly reducing the increase in the storage modulus.

[0113] The role of flexible monomers cannot be ignored either. The low-temperature performance of Comparative Example 4 illustrates the direct consequence of insufficient flexible monomers. At -60°C, the storage modulus of Comparative Example 4 is 245.3MPa, which is significantly higher than 221.5MPa of Example 2. The core reason for this difference lies in the long-chain structure introduced by the flexible monomer. It lowers the glass transition temperature of the material, increases the activity of the molecular chain, and allows Example 2 to maintain a high degree of flexibility in a low-temperature environment. However, the content of flexible monomers in Comparative Example 4 is insufficient, and the molecular chains become more rigid, which ultimately leads to a significant deterioration in low-temperature flexibility.

[0114] The performance of the comparative example 1 and 2 compared to the comparative example further verified the synergistic effect of the dynamic crosslinker and the flexible monomer. The dynamic crosslinking network provides structural flexibility, and the flexible monomer enhances the deformation ability through segment softening. The lack of a single effect in the comparative example makes the material more rigid at low temperatures and unable to cope with complex external deformation requirements. This rigid feature makes it difficult for the comparative example to meet practical applications in extreme environments.

[0115] Experiment 3: High temperature mechanical properties test Experimental description: Experimental purpose: To test the mechanical properties of the examples and comparative examples under high temperature conditions, and to evaluate the role of dynamic crosslinkers and flexible monomers in improving high temperature stability and flexibility.

[0116] Experimental samples: Embodiment: Embodiment 1, Embodiment 3 Comparative Examples: Comparative Example 1 (without dynamic crosslinking agent), Comparative Example 4 (with reduced flexible monomer content) Experimental equipment: universal material testing machine (tensile test mode), high temperature environmental chamber (temperature control range from room temperature to 300°C).

[0117] Experimental steps: Sample preparation: Standard tensile specimens were prepared with dimensions of 100 mm × 10 mm × 2 mm.

[0118] The samples were dried at 50°C for 12 h to eliminate the interference of moisture in the samples on the test.

[0119] Experimental conditions: The test temperature of each group of samples was set at 250°C, and the loading method was stretching to fracture.

[0120] The initial clamping distance is 80 mm and the loading speed is 10 mm / min.

[0121] Testing process: The sample was placed in a high temperature environment box, preheated to the test temperature of 250°C, and kept at a constant temperature for 3 minutes to stabilize the sample temperature.

[0122] Turn on the universal material testing machine to perform a tensile test, and record the tensile strength (MPa) and elongation (%) in real time until the sample breaks.

[0123] Each group of samples was tested 3 times and the average value was taken.

[0124] Data processing: Analyze the tensile strength and elongation of different samples, and compare their mechanical stability and flexibility under high temperature conditions.

[0125] Experimental data: Table 3: Comparison of tensile properties of the embodiments and comparative examples at 250°C Sample No. Tensile strength (MPa) Repeat test 1 Repeat Test 2 Repeat test 3 Elongation (%) Repeat test 1 Repeat Test 2 Repeat test 3 Example 1 28.5 28.2 28.9 28.4 72.1 70.8 73.2 72.4 Example 3 27.1 27 27.5 26.9 68.4 67.5 69.8 67.8 Comparative Example 1 15.6 15.2 16.1 15.5 23.7 22.8 24.1 24.3 Comparative Example 4 19.3 19 20.2 18.9 31.6 30.5 32.1 32.3 Summary: Under high temperature conditions, the influence of dynamic cross-linking agents is obvious. The tensile strength of Comparative Example 1 is only 15.6MPa, almost half of that of Example 1. The lack of a dynamic cross-linking agent causes the molecular chains of the material to lose constraints at high temperatures, making it prone to irreversible segment slippage, which ultimately manifests as a significant decrease in mechanical properties. In contrast, Example 1 provides additional support capacity for the material through the breaking and recombination mechanism of dynamic bonds. This dynamic regulation can obviously effectively alleviate the problem of stress concentration and enhance structural stability in high temperature environments.

[0126] The performance of the flexible monomer at high temperature is reflected in its ductility. The elongation of Comparative Example 4 is only 31.6%, which is much lower than 68.4% of Example 3. When the flexible monomer is insufficient, the molecular chain is too rigid to withstand the effects of external stress. In Example 3, the flexible monomer disperses the stress concentration during high-temperature stretching through its soft molecular chain segments, significantly improving the ductility of the material. This flexible adjustment mechanism allows Example 3 to still exhibit good toughness under high temperature conditions, while Comparative Example 4 quickly loses its deformation ability at high temperatures.

[0127] The overall results of high-temperature mechanical properties show that there is a good synergy between the dynamic crosslinker and the flexible monomer. The examples show higher tensile strength and elongation under high temperature conditions, while the lack of a single factor in the comparative example leads to a sharp drop in performance. This difference stems from the optimized design of the molecular chain structure. The dynamic crosslinking network provides stability, while the flexible monomer makes the material adaptable at high temperatures. The rigid segments of the comparative example lack the ability to adjust, and this fundamental deficiency is particularly evident in the experimental data.

[0128] Experiment 4: Long-term aging resistance test Experimental description: Experimental purpose: Through high temperature aging test, the long-term high temperature environment stability of the examples and comparative examples is evaluated, and the role of dynamic cross-linking agents and functionalized nanoparticles in enhancing the anti-aging performance of materials is verified.

[0129] Experimental samples: Embodiment: Embodiment 1, Embodiment 2 Comparative Examples: Comparative Example 2 (non-functionalized nanoparticles), Comparative Example 5 (nanoparticles with larger particle size) Experimental equipment: high temperature constant temperature box (temperature control range from room temperature to 400℃), universal material testing machine (tensile test mode).

[0130] Experimental steps: Sample preparation: Samples were prepared according to the recipes and processes of the examples and comparative examples, including sheets with a size of 50 mm×50 mm×2 mm and standard tensile specimens (100 mm×10 mm×2 mm).

[0131] The samples were dried at 50 °C for 12 h to ensure that no moisture remained.

[0132] Aging test: Each group of samples was placed in a high temperature constant temperature box with the temperature set at 300°C and the exposure time being 100 h.

[0133] Take out a group of samples every 20 hours for performance testing, observe the surface state of the material and record the tensile properties.

[0134] During the aging process, the samples were closely observed for color changes, crack formation, and surface blistering.

[0135] Performance Test: After aging, the samples were cooled to room temperature and the tensile properties were tested.

[0136] The tensile strength (MPa) and elongation (%) of the samples before and after aging were measured using a universal material testing machine.

[0137] Each sample was tested 3 times and the average value was taken.

[0138] Data processing: Compare the change rate of tensile properties before and after aging of the samples of the examples and comparative examples; Analyze the differences in surface conditions and evaluate the samples' anti-aging capabilities.

[0139] Experimental data: Table 4: Comparison of aging performance of examples and comparative examples

[0140] Summary: The role of functionalized nanoparticles is very intuitive in the aging process. After 100h aging, the tensile strength of Comparative Example 2 is only 9.5MPa, while Example 1 can still maintain 23.9MPa. In Comparative Example 2, which lacks functionalized nanoparticles, the molecular segments lose stable support during the aging process, and the cracks expand rapidly and penetrate the material. The functionalized nanoparticles in Example 1 stabilize the microstructure of the matrix through good dispersibility, and the maze effect of the nanoparticles also greatly slows down the propagation rate of the cracks.

[0141] The influence of particle size cannot be ignored either. The performance of comparative example 5 decreases significantly faster than that of example 2, and the tensile strength is only 12.7MPa after 100h. Nanoparticles with larger particle sizes are unevenly dispersed in the matrix, forming stress concentration points. These defects quickly become the starting point of cracks during the aging process, causing the material structure to collapse. In example 2, the nanoparticles with a particle size controlled at 30nm can be evenly distributed in the matrix, forming a better interface bond with the molecular chain, so that the material exhibits higher anti-aging ability.

[0142] The dynamic cross-linking network also plays a key role in improving the aging performance. The performance of Example 1 and Example 2 are both better than the comparative example, especially in the tensile properties after long-term aging. The dynamic cross-linking agent delays the irreversible degradation of the molecular chain during the aging process through its reversible breaking and recombination mechanism. This dynamic adjustment ability effectively slows down the formation and expansion of cracks, making the aging process of the embodiment slower, while the materials lacking this mechanism in the comparative example quickly lose their performance. The synergistic effect of functionalized nanoparticles and dynamic cross-linking agents provides a solid foundation for the anti-aging performance of the material, and this synergistic effect cannot be achieved in the comparative example.

[0143] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A soft, low-fluorine overflow X-ETFE insulating material, characterized in that: The composition includes the following components, which are composed by mass percentage: 75-85% of X-ETFE resin, 5-8% of dynamic cross-linking agent, 3-6% of functionalized nanoparticles, 1-3% of fluorine capture agent, 5-8% of flexible monomer and 1-2% of flame retardant.

2. A soft, low-fluorine overflow X-ETFE insulating material according to claim 1, characterized in that: The dynamic cross-linking agent is a compound containing an imine group or a disulfide bond.

3. A soft, low-fluorine overflow X-ETFE insulating material according to claim 1, characterized in that: The functionalized nanoparticles are boron nitride, graphene oxide or silicon dioxide, and the particle size thereof is 20-50 nm.

4. A soft, low-fluorine overflow X-ETFE insulating material according to claim 1, characterized in that: The flexible monomer is polydimethylsiloxane.

5. The soft, low-fluorine overflow X-ETFE insulating material according to claim 1, characterized in that: The fluorine scavenger is an amino compound or a zinc complex.

6. A method for preparing a soft, low-fluorine overflow X-ETFE insulating material, characterized in that: The following steps are involved: S1. Functionalized nanoparticle treatment: surface functionalization of the nanoparticles to enhance their compatibility with the X-ETFE resin; S2, raw material mixing: X-ETFE resin, dynamic cross-linking agent, flexible monomer, functionalized nanoparticles and fluorine capture agent are uniformly mixed according to the mass percentage ratio; S3, melt blending: melt blending the mixture in a twin-screw extruder at an extrusion temperature of 200-260° C. and a screw speed of 50-150 rpm; S4, dynamic crosslinking reaction: subjecting the melt blended materials to dynamic crosslinking reaction at 260-300°C for 10-15 minutes; S5. Molding and cooling: After molding, the material is quickly cooled, and the temperature of the cooling medium is -10℃ to 0℃.

7. The method for preparing a soft, low-fluorine overflow X-ETFE insulating material according to claim 6, characterized in that: The functionalized nanoparticle treatment in step S1 includes the following process: S1.1, adding nanoparticles into deionized water and stirring to form a suspension; S1.2, adding silane coupling agent for surface modification, the reaction temperature is 50-60℃, the pH value is 4-6, and the time is 6-8h; S1.3, washing and vacuum drying to obtain functionalized nanoparticles.

8. The method for preparing a soft, low-fluorine overflow X-ETFE insulating material according to claim 6, characterized in that: The raw materials in step S2 are mixed in a high-speed mixer with a rotation speed of 1000-2000 rpm and a mixing temperature of room temperature to 60°C.

9. The method for preparing a soft, low-fluorine overflow X-ETFE insulating material according to claim 6, characterized in that: The temperature of the twin-screw extruder for melt blending in step S3 is distributed along the axial direction as follows: 200-220° C. in the feeding zone, 220-240° C. in the mixing zone, and 240-260° C. in the discharge zone.

10. The method for preparing a soft, low-fluorine overflow X-ETFE insulating material according to claim 6, characterized in that: The cooling medium in step S5 is cooling liquid or air, and the cooling time is 10-20 minutes.